Production of ethyl alcohol from plants of the Asteraceae family - Azimbayeva, G. E.; Kamysbayeva, A. K.; Sagimbayeva, A. E.; Yessenova, M. D.; Bakibaev, Abdigali A. (Biomass conversion and biorefinery)
The alcohol industry is material-intensive, where the cost of grain on the production of ethyl alcohol exceeds 60% of the total production costs. The most effective way to use agricultural raw materials is the introduction of new plants. Plants from the Asteraceae family are a promising alternative source due to their inulin content that can be used for ethyl alcohol production. However, the fermentation of alternative raw materials might bring undesirable sub-products that compromise the quality of the ethyl alcohol, such as fuse oil, ester, and aldehyde. This article aims to obtain ethyl alcohol from four alternative plants that belong to the Asteraceae family. To do so, we evaluated the ethyl alcohol production from raw materials from four different plant species from the Asteraceae family: Helianthus tuberosus L., Dahlia, Cichorium intybus L., and Arctium lappa L. Our findings revealed that, after the first distillation, the alcohol content ranged between 5 and 12%. The concentration of waste products (fuse oil, ester, and aldehyde) can decrease to 1519 mg dm−3 after adsorption with activated carbon and calcium oxide. Therefore, those four plants are viable alternatives to alcohol production due to their inulin content. These alternative plant materials can improve the state of the alcohol and alcoholic beverage industry, and the introduction of new technologies presented here can potentially increase the profitability of bioethanol production.